Data Sharing using PDPA-Compliant Blockchain Architecture in Malaysia - Baskaran H.; Yussof S.; Bakar A.A.; Rahim F.A. (Science and Information Organization, 2024)
Data privacy is undoubtedly the biggest concern for the modern society. Data privacy is also becoming a key policy in data protection regulations. Organizations assemble massive amount of personal data of the users for monetary and political purposes. These data can be sold for commercial purpose without the prior knowledge or permission from the respective data owners. This can be mitigated by having blockchain to provide a much-needed transparency. However, blockchains own transparency becomes its own disadvantage when data owners want to be completely anonymous. Blockchains transparent nature will be conflicting with non-linkability. Since the data in blockchain is publicly viewable, any personal data or private transactions being processed through blockchain will be exposed to every node in the network. Hence, blockchain implementations also must comply with privacy acts such as Personal Data Protection Act (PDPA) to have privacy by design and by default. Hence, this paper proposes a PDPA-compliant blockchain architecture for data trading that provides complete control of data and anonymity to the users. A prototype is created using various tools to implement the proposed architecture. This study presents anonymous data sharing for users, data access, data delete features to verify the correctness of the proposed architecture. 2023, International Journal of Advanced Computer Science and Applications.All Rights Reserved.